The Intertwined Trajectory between Gender and Psychic Anxiety in Chimamanda Ngozi Adichie’s Americanah - misanjas, misanjas; Ali Mhodar, Tahseen; Ali Abdulhasan, Hayder ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This paper examines the intersection between gender and the physic aspects of anxiety in Chimamanda Ngozi Adichie’s Americanah (2013). The study focuses on how Adichie looks into gender through psychological perspectives. The main argument of the study will be the interpretation of gender as an impasse negatively affecting the novel’s female protagonist’s psyche. Ifemelu, who is the chief protagonist, embodies Adichie’s concern with creating an optimal view of women on the brink of psychological retardation due to two interrelated problems. The first problem gender severe prejudice engulfing women’s social relations. The second problem is women’s development of psychic anxiety as a result of the gender bias. Therefore, the study’s objective is to explore gender discriminations as the primary cause of protagonist’s psychic anxiety. The methodology for analyzing the relationship between gender and anxiety will be qualitative. It follows a textual analysis of the major female protagonist as well as the novel’s setting which plays a crucial role in identifying the accumulative formation of the protagonist’s anxiety. Thus, the study’s finding will be limited to the exploration of gender discrimination as an impetus to the formation of human anxiety.